Patients’ perceptions of podoconiosis causes, prevention and consequences in East and West Gojam, Northern Ethiopia - Molla Yordanos B; Tomczyk Sara; Amberbir Tsige; Tamiru Abreham; Davey Gail (BMC Public Health, 2012)
Abstract Background Podoconiosis is a form of non-filarial elephantiasis that affects barefoot individuals in highland tropical areas. The disease presents with bilateral, asymmetric swelling of the legs, usually confined to below the knee. This study aimed to assess podoconiosis patients’ perceptions of prevention, control, causes and familial clustering of the disease, and to document physical, social and economic impairments associated with the disease, with the ultimate aim of enabling development of tailored interventions in this region. Methods This descriptive study is part of the largest cross-sectional community-based household survey yet conducted on podoconiosis. It was completed in November and December, 2011, in Debre Eliyas and Dembecha Woredas of East and West Gojam Zones, northern Ethiopia, and consisted of a house-to-house census by community health workers followed by interviews of identified patients using a structured questionnaire. Results In the 17,553 households surveyed, 1,319 patients were identified. More male as compared to female patients were married (84.6% vs. 53.6%, χ2 = 157.1, p < 0.0001) while more female as compared to male patients were divorced (22.5% vs. 3.6%, χ2 = 102.3, p < 0.0001). Less than half of the study subjects believed podoconiosis could be prevented (37.5%) or controlled (40.4%) and many (41.3%) did not know the cause of podoconiosis. Two-fifths of the study subjects had a relative affected with podoconiosis. Approximately 13% of the respondents had experienced one or more forms of social stigmatization. The coping strategies adopted by patients to mitigate the physical impairments caused by podoconiosis were: working only occasionally (44.9%), avoiding physically demanding tasks (32.4%), working fewer hours (21.9%) or completely stopping work (8%). Most study subjects (96.4%) had noticed a decline in their income following the development of podoconiosis, and 78% said they were poorer than their healthy neighbours. Conclusion This study shows that podoconiosis has strong psychosocial, physical and economic impacts on patients in East and West Gojam Zones of northern Ethiopia. Concerns related to familial clustering, poor understanding of the causes and prevention of podoconiosis all add to the physical burden imposed by the disease. Strategies that may ease the impact of podoconiosis include delivery of tailored health education on the causes and prevention of disease, involving patients in intervention activities, and development of alternative income-generating activities for treated patients.